Determination of Late Spring Frost Affections on Some Grape Varieties Grown in Samsun - Bülent KÖSE; Seda ATEŞ; Hüseyin ÇELİK (Türkiye Tarımsal Araştırmalar Dergisi, 2014)
Determining the climatic factors of viticultural areas have great importance. The late spring frost cause significant amount of economic losses in some years in many of areas. In March and April of 2014 has experienced frost damage in many parts of our country. Although Samsun coastal zone has the Black Sea region climate, in some years late spring frost causes economic losses in some important products. In this study, several grape varieties grown in the research and application vineyard located in The Ondokuz Mayıs University Campus area have studied to determine the frost damage by the late spring frost. In the present study, Yalova İncisi, one of the early grape variety has at least frost damage, Çavuş and Trakya İlkeren grape varieties has the most frost damage.